2016
DOI: 10.1111/iej.12648
|View full text |Cite
|
Sign up to set email alerts
|

Impact of needle insertion depth on the removal of hard‐tissue debris

Abstract: The insertion depth of irrigation needles significantly influenced the removal of hard-tissue debris. A needle tip positioned 1 mm short of the WL resulted in percentage levels of hard-tissue debris removal almost three times higher than when positioned 5 mm from the WL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 39 publications
(106 reference statements)
2
30
0
5
Order By: Relevance
“…A recent micro‐CT study also demonstrated a significant influence of the needle insertion depth on the removal of AHTD from isthmus‐containing mesial root of mandibular molars (Perez et al . ). Positioning of the irrigation needle at 1 mm short of WL resulted in percentage levels of AHTD removal almost three times higher than an insertion depth of 5 mm from the WL (Perez et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent micro‐CT study also demonstrated a significant influence of the needle insertion depth on the removal of AHTD from isthmus‐containing mesial root of mandibular molars (Perez et al . ). Positioning of the irrigation needle at 1 mm short of WL resulted in percentage levels of AHTD removal almost three times higher than an insertion depth of 5 mm from the WL (Perez et al .…”
Section: Discussionmentioning
confidence: 97%
“…Positioning of the irrigation needle at 1 mm short of WL resulted in percentage levels of AHTD removal almost three times higher than an insertion depth of 5 mm from the WL (Perez et al . ). However, no other studies are available comparing manual irrigation and different activation techniques for the removal of AHTD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The lack of standardization in how the individual IATs were used does not allow for comparisons to be made between techniques. Factors such as insertion depths (Sedgley et al 2005, Boutsioukis et al 2010, Perez et al 2017, power intensities (Jiang et al 2011) andcanal taper (de Gregorio et al 2013) all impact the degree of smear layer and debris removal. Significant variations in these features as well as activation time and file type were found to be present in the studies included in this review (Table 5).…”
Section: Efficacy Of Individual Iatsmentioning
confidence: 99%
“…Although both techniques have very low spatial resolution (ranging from 100 to 1000 μm), radiographs have also de limitation of being a bidimensional evaluation. Moreover, major differences in the root canal anatomy among the used specimens (lack of paired specimens) may be a source of bias in evaluating the effectiveness of a certain technique in endodontic studies and for this reason, the use of prototypes, with individualized root canal anatomy may bring advantages in this regard. Finally, a detailed quantitative tridimensional analysis of voids and effectiveness of root canal obturation in primary teeth have not yet been performed.…”
Section: Introductionmentioning
confidence: 99%